Research on modes and operating parameters of construction mixes preparing equipment - Rudyk, Rostyslav; Bidanets, Serhii (Academic journal Industrial Machine Building Civil Engineering, 2023)
This research paper examines the various modes and parameters of operation of equipment used for preparing mortars in the construction industry. The study emphasizes the significance of ensuring the proper functioning of mixers and mixers on construction sites, as it directly affects the time and energy consumption involved in mortar preparation. The paper discusses different types of mixers, including gravity mixers and concrete mixing buckets, and provides an analysis of their advantages and disadvantages. Additionally, the research presents calculations and formulas for determining the power consumption and energy efficiency of mixers. The findings of the study highlight the necessity for a scientific approach in selecting components based on their energy efficiency in construction site conditions. By considering energy efficiency, construction professionals can optimize the performance of mixers and reduce energy consumption, leading to cost savings and environmental benefits. This research contributes to the existing knowledge in the field and provides valuable insights for decision-making in the selection and operation of mortar preparation equipment in the construction industry.